Reconstructive Endovascular Treatment of Intracranial Fusiform Aneurysms: A 1-Stage Procedure with Stent and Balloon - Suh, S.H. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: Intracranial fusiform aneurysms, which incorporate the branch vessel and require salvaging of the parent vessel, are difficult to manage. The goal of this study was to evaluate the efficacy of reconstructive endovascular treatment of intracranial fusiform aneurysms by using a 1-stage procedure with a stent and balloon. MATERIALS AND METHODS: During a 3-year period, 20 patients with 20 intracranial fusiform aneurysms were treated by using a 1-stage procedure involving a balloon and stent. Subarachnoid hemorrhage was present in 15 patients. Five aneurysms were located in the anterior circulation and 15, in the posterior circulation. Clinical outcomes and periprocedural complications were evaluated in all patients. The extent of coil packing was evaluated by control angiography after embolization and classified as either complete occlusion or partial occlusion. Angiography was performed 6, 12, and 24 months after embolization to evaluate stent patency and coil packing. RESULTS: The 1-stage procedure by using a combination of balloon and stent was technically successful in all patients. There were no complications related to the procedure, complete occlusion was obtained in 16 patients, and partial occlusion, in 4 patients. All patients recovered well except for 2 who died due to causes unrelated to the procedure. Clinical follow-up was performed in all surviving patients at a mean of 12.3 months (range, 7–24 months), and angiography showed that the patent parent arteries were free of aneurysm recanalization or in-stent stenosis. CONCLUSIONS: This 1-stage procedure may provide a feasible and safe treatment strategy for the management of intracranial fusiform aneurysms that are not amenable to deconstructive embolization.